PARADIGMA PERUBAHAN STRUKTUR FONOLOGIS KATA BERPOLA DASAR KV-KV DALAM BAHASA DAWAN (Sebuah kajian Linguistik Struktural) - Semuel Nitbani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2021)
The sentence structure wants its constituent units to fulfill grammatical and fontological requirements so that the sentence becomes a language unit that is able to express the intended meaning in communication. In Dawan's language, the phonological structure of words plays a role in producing grammatical units both at the morphological level (word formation) and at the syntactic level (formation of phrases, and clauses) in sentence formation through slipping, shifting phoneme positions, changing phoneme positions with substitutions. phoneme. This phenomenon is complex in Dawan's language. This paper only discusses changes in the phonological structure consisting of 2 syllables with a CV-CV pattern, with the vowel in the first syllable being the same as the vowel in the second syllable (V1 = V2), and words with a CV-CV pattern with different vowels in the first syllable. with a vowel in the second syllable (V1 V2). Deletion occurs in words with the pattern V1 = V2, and also applies to the pattern V1 V2 with V1 = e, V2 = i; V1 = o, V2 = a; V1 = i, V2 = a; V1 = e, V2 = a. The displacement of the phonemes occurs in the V1 V2 pattern with V1 = a, V2 = i; V1 = a, V2 = u; V1 = a, V2 = e; V1 = a, V2 = o. The displacement of the phoneme position with the change of the V2 phoneme occurs in the V1 V2 pattern with e → i, i → e, o → u. Changes with the punctuation pattern into a word consisting of 2 syllables with a CV-CV pattern into 1 syllable with a CVC pattern. Likewise, changes to changes both with phoneme changes and without phonemes make vowels (V2) shift from vowels to semivowels so that words that previously consisted of 2 syllables with a CV-CV pattern of 1 syllable with a CVVC pattern. The depiction of 2 vowels in the CVVC pattern shows that V2 does not lose its phonemic loss in this process.